The Effect of Planting Period, Seed and Mineral Fertilizers on Harvest Elements and Yield of Trikale "Sardor" Variety (Texas Journal of Agriculture and Biological Sciences, 2023)
In this article, the effect of planting time, seed and mineral fertilizer rates on yield elements and grain yield of triticale "Sardor" variety in the conditions of dry typical gray soils of Jizzakh region is studied.